Book Reviews - Huang, Alexander C. Y.; Mondal, Sandip; Sriwastav, Sharmistha Chatterjee; Giza, Natalia; Kawachi, Yoshiko (Multicultural Shakespeare: Translation, Appropriation and Performance, 2012)
Diana E Henderson, Collaborations with the Past: Reshaping Shakespeare across Time and Media, Ithaca: Cornell University Press, 2006. Pp. xi + 289. ISBN 978-0801444197. Vintage Shakespeare: New Perspectives From India and Abroad, eds. Prashant K. Sinha and Mohini Khot, Jaipur: Book Enclave, 2010. Pp. 240. ISBN 978-81-8152-271-9. The Tempest by William Shakespeare, ed. Sarbani Chaudhury, New Delhi: Pearson Longman, 2009. Pp. Liii +217. ISBN 978-81-317-0981-8. Elżbieta Stanisz, Kierunki Polskiej Szekspirologicznej Myśli Krytycznej w Dwudziestoleciu Miedzywojennym (1918-1939) [Shakespearean Criticism in Poland in the Inter-War Period], Toruń: Wydawnictwo Adam Marszałek, 2011. Pp. 290. ISBN 978-83-7611-887-1. Shakespeare: The Indian Icon, ed. Vikram Chopra, New Delhi: The Readers Paradise, 2011. Pp. xxvi + 836. ISBN 978-81-920751-2-9